A Phenomenology of Project Based Learning in Vocational Analytical Chemistry Education - Silvia, Debora; Munzil, Munzil; Yahmin, Yahmin (Universitas Negeri Medan, 2025)
This study aims to explore the challenges, strategies, and impacts of implementing Project-Based Learning (PjBL) in the Analytical Chemistry program at Vocational High Schools (SMK). Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation involving teachers and students actively engaged in PjBL activities. The analysis followed Moustakas’s phenomenological steps, including data reduction, categorization, and interpretation. The findings revealed three key themes: (1) resource and infrastructure limitations, (2) teachers’ adaptive and innovative strategies, and (3) students’ creativity and entrepreneurial motivation. Despite facing financial and facility constraints, teachers demonstrated resilience by utilizing local resources, modifying learning designs, and applying reflective assessment. Students, in turn, showed high creativity and problem-solving skills by developing innovative chemical-based products that integrated environmental awareness and entrepreneurship. The study concludes that PjBL effectively enhances students’ higher-order thinking, creativity, and motivation in vocational chemistry learning. However, its sustainability depends on institutional support, adequate funding, and collaboration with industry. These findings highlight the importance of developing structured, project-based digital modules to strengthen teacher competence and ensure meaningful, future-oriented learning in vocational education.